Telehealth and oropharyngeal dysphagia: An integrative review - Nataly Santana de Araújo; Raíssa Gomes Magalhães; Camila de Alencar Frois; Laura Davison Mangilli (Revista CEFAC, 2023)
ABSTRACT Purpose: to analyze the telehealth speech therapy approach in patients with oropharyngeal dysphagia and determine the applications and effects of this practice. Methods: the following descriptors were used for selection: Telerehabilitation, Telemedicine, "Remote Consultation", "Healthcare Delivery", "Distance Counseling", "Therapy, Computer-Assisted", "Speech-Language Pathology", "Speech Therapy", "Swallowing Disorders", Dysphagia, “Bottle Feeding" and "Enteral Nutrition” in PubMed, MedLine, Scopus and Web of Science databases and in the gray literature, by Google Scholar and ProQuest. Studies were selected without time limits, in Portuguese, English and Spanish, that described the applicability and/or effects of telehealth in speech therapy practice in patients with swallowing disorders/dysphagia, regardless of gender and age. For analysis, the following were considered: level of scientific evidence and recommendation, telehealth modality, objectives, methods and results/conclusion. Literature Review: 490 articles were found and, after exclusion of duplicates, analysis of titles, abstracts and reading of full articles, 22 studies were selected. The articles were classified into telehealth modalities: tele-education, telediagnosis, teleconsulting, teleregulation and telemonitoring. Conclusion: the telehealth modalities described had a great potential to promote significant improvements in patients presented with swallowing disorders/dysphagia, suggesting them as viable for speech therapy services. Among them, teleconsultation was the least addressed.